Agricultural challenges today and in the future: the beneficial role of agroecology - Keay, Gordon (Cranfield University, 2009)
Interest in agroecology is growing as evidence mounts that conventional agricultural methods are unsustainable, degrading the resource base (e.g. soil, water, crop diversity, biodiversity etc.) on which they depend. Alternative ways to produce foods that build soil fertility, protect ecosystems, conserve biodiversity and reduce energy inputs, provide the possibility of long-term productivity and ecological sustainability. The International Assessment of Agricultural Science and Technology for Development (IAASTD) have supported agroecology as a key set of solutions for world agriculture, which synergistically tackle development, sustainability and conservation goals. This study presents indicators to measure the sustainability of an agricultural practice which, placed in a hierarchical pyramid, demonstrates their importance and interconnected relationships. A comparative evaluation of agroecological and conventional systems is shown to assess the effects of management practices on the indicators. Agroecological approaches differ from conventional ones as they aim to sustain the soil and ecosystems by reducing synthetic inputs and creating alternative natural processes to maintain soil fertility and manage pests. Soil fertility is the essential indicator of sustainable agriculture, it was shown to improve in agroecological systems, indicated through increased soil microbial biomass (60% higher than in conventional agriculture) and earthworm abundance (up to 88% higher than in conventional agriculture). The loss of biodiversity due to current intensive farming practices is an indicator of unsustainability. In the agroecological systems biodiversity was shown to be comparatively higher. The diversity of bird and beetle species were recorded to be 50% and 38% more abundant respectively, and bat activity was shown to be 60% higher. These are bio-indicators of sustainable agriculture. The reduced chemical inputs led to an average of 50% less energy used on the agroecological systems. The resulting effects on yields showed great variation. One long term trial showed a 20% yield reduction in the agroecological system. Yet in times of drought, when advanced cropping systems were implemented, in developing countries yields were shown to be comparable, often significantly higher. This study provides solid evidence that the world’s future food security lies in the hands of sustainable agricultural practices. Agroecology demonstrates techniques that can be used towards reaching this vital goal.
Keywords: Agroecology; Sustainable Agriculture; Sustainability Indicators; Soil fertility; Biodiversity; Energy efficiency